Analysıs Of Islamıc Hıgher Educatıon Development Models In Indonesıa - Ika Kartika; Yanti Hasbian Setiawati; Saepudin Saepudin; Arman Aria Sunasa; Nova Dahliah Susanti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to find out and analyze the development model of Islamic Higher Education in Indonesia The method used in this study is the literature method, which is to review and analyze written sources about various strategic actions about the development of Islamic Higher Education in Indonesia. The results showed that the development of the PTAI model can be analyzed through two approaches: First, the organic approach, which is the approach used to analyze the development of PTAI, namely the development of PTAI can develop its institutions in accordance with the demands of community needs and in line with the development of science and technology. This is because the university has state status, is funded by the government, and receives financial support and human resources in accordance with development needs. Secondly, the mechanical approach is a model of approach that is based on natural change and what it is. The mechanical approach model can be used as a tool to analyze the development of private PTAI, namely PTAI which is managed by the private sector and experiences many obstacles in its management caused by limited sources of funds, limited development facilities, and infrastructure. and management of limited human resources. This resulted in private PTAI developing slowly in improving its academic quality.